2019
DOI: 10.1101/856658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changing environments reveal innovative genetic variation in children’s cortisol responses

Abstract: Genetic associations with biopsychosocial phenotypes are often interpreted as evidence that the genome codes for fixed end-states. Instead, a given genotype might regulate a dynamic range of phenotypes in response to environmental change. We collected hair cortisol (n = 1,104), salivary cortisol in reaction to an in-laboratory stressor (n = 537), and diurnal salivary cortisol (n = 488) from twins aged 8-15 years in the Texas Twin Project. Baseline genetic variation in both salivary and hair cortisol was not si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…First, girls were more reactive to stress than boys: They reported higher subjective stress increases following stress exposure, and had higher cortisol stress responses. Several previous studies have reported higher cortisol stress responses in girls than boys, although the evidence overall is mixed and should be explored meta-analytically (Gunnar et al, 2009;Hatzinger et al, 2007Hatzinger et al, , 2013Hostinar et al, 2015;Quesada et al, 2012;Raffington et al, 2019;Räikkönen et al, 2010;Stroud et al, 2009;Yim et al, 2010).…”
Section: Effects Of Stress Exposure and Associations With Cortisolmentioning
confidence: 98%
“…First, girls were more reactive to stress than boys: They reported higher subjective stress increases following stress exposure, and had higher cortisol stress responses. Several previous studies have reported higher cortisol stress responses in girls than boys, although the evidence overall is mixed and should be explored meta-analytically (Gunnar et al, 2009;Hatzinger et al, 2007Hatzinger et al, , 2013Hostinar et al, 2015;Quesada et al, 2012;Raffington et al, 2019;Räikkönen et al, 2010;Stroud et al, 2009;Yim et al, 2010).…”
Section: Effects Of Stress Exposure and Associations With Cortisolmentioning
confidence: 98%